The specificity of the double simple imitation and its role in the dramaturgy of the Renaissance epoch musical works - Bozanic, Zoran (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. Dramaturgy of the vocal works from the Renaissance epoch, connected to the application of the specific ways of counterpoint work, thus far hasn’t been studied more thoroughly. Yet, the manifestation of some of the dramatic principles can also be noticed in music of this period. It is specially relevant at presentation of the two themes in simultaneous sounding. In that context, the specificities of musical dramaturgy realization by use of the simple imitation are little known. Main objective of the study is to light up the distinctiveness of the double simple imitation in the austere style music and to examine its reference to convertible counterpoint. On the other side, the influence of the counterpoint technique on the dramaturgy of Renaissance musical work will be opened. Methodology is based on the examples analysis from Palestrina creative work. How the study was done. In chosen analytical specimens, the ways of counterpoint work was identified and defined along with the definiteness of their dramaturgic function in the context entirety. Results and conclusions. The double simple imitation leads to various possibilities of the imitation voices combination, specially in situations when the themes length is dissimilar. The convertible counterpoint, which then appears might be interpreted by methods used at unimitated polyphony. On the other side, such application of the polythematic imitation might be in function of the musical form dramaturgy. Through the various spatial changes of the thematic material within composition entirety specific section, the clear separation of thematic material occurs in relation to the other, monothematic sections; it is experienced as the focus of composition. By beforehand planned way of work with the themes, the clear movement architectonics is created. Practical significance. The work shows the way of the simple imitation interpretation based on two themes. Additionally, this research opens up the possibility of dramaturgy use as analytical practice instrument and also in vocal works of the old counterpoint masters.